MutaRNA: analysis and visualization of mutation-induced changes in RNA structure - Miladi, Milad; Raden, Martin; Diederichs, Sven; Backofen, Rolf (Nucleic acids research, 2020)
Abstract. RNA molecules fold into complex structures as a result of intramolecular interactions between their nucleotides. The function of many non-coding RNAs